Teachers' attributes and academic performance of students - Velasco, Elsie N. (Animo Repository, 2013)
Given the marked difficulties of first year accountancy students in basic accounting courses in Ramon V. del Rosario, College of Business, De La Salle University, as evidenced by high attribution rates in the grading reports of teachers handling basic accounting, this study attempts to identify the accounting teachers' negative attributes that may have significant correlation to academic performance of students. Academic performance of students is measured by their success or failure in two previous basic accounting courses. In this study, it is measured specifically using the student's grade point average (GPA) in two basic accounting courses. Purposive sampling was carried out to 89 first year accounting major students enrolled in their third basic accounting course during the third term of academic year (AY) 2013-2014, De La Salle University (DLSU), These teachers' attributes comprised the following: inadequacy of motivational techniques, not being readily available for students's consultations, does not show evidence of mastery of subject matter, learning objectives not reflected in exams and other evaluative measures, poor communication skills, not well prepared for class, poor rapport with the students and lack of concern for students' welfare. The study also examined if male and female students' perception on teachers' attributes differ significantly from each other, Non-parametric test using Spearman's rho correlation was used to determine the strength of correlation between teachers' attributes and students' performance. Findings revealed that only one attribute exhibited significant correlation with students' performance and that is lack of concern for students' welfare. Further, findings also show that gender does not affect the perception of students with respect to negative teachers' attributes as shown by the t-test result.